Efficient management of rheumatoid arthritis significantly reduces long-term functional disability. Issue 8 (30th October 2007) - Tanaka, E; Mannalithara, A; Inoue, E; Hara, M; Tomatsu, T; Kamatani, N; Singh, G; Yamanaka, H
Abstract : Objectives: The aim of this study was to examine the effect of efficient management of rheumatoid arthritis (RA) in relation to disability levels in a large cohort of patients with RA over a period of 3 years. Methods: We studied 2775 patients with RA who had continuous enrolment for at least 3 years from 7511 patients with RA enrolled in an observational cohort study (Institute of Rheumatology, Rheumatoid Arthritis (IORRA)) from October 2000 to April 2005. The 28-joint Disease Activity Scores (DAS28) were calculated at 6 month intervals for all the patients and a value <2.6 was considered as a tight control. We have set up a new variable for each patient, "Avg-Dscore", based on the transition of each patient's DAS28 value, taking the threshold level of 2.6 into consideration. The "Avg-DAS28" is the average of DAS28 values over all the phases. Functional disability status was assessed by J-HAQ, the validated Japanese version of the Health Assessment Questionnaire (HAQ). The relationship of "Avg-Dscore" and "Avg-DAS28" with the functional disability level was determined using Spearman correlation coefficients and multiple linear regression models. Results: The baseline features of these 2775 patients were: female 83.7%, mean age 56.8 years, mean RA duration 9.5 years, mean initial DAS28 4.0, mean initial J-HAQ score 0.79, and mean final J-HAQ score 0.86. There was a statistically significant correlation between "Avg-DAS28" and final J-HAQ score (r = 0.57, p<0.001), indicating that tighter disease control has significant association with lower disability levels. A similar relationship was observed between "Avg-Dscore" and final J-HAQ score (r = 0.47, p<0.001). Multiple linear regression analysis, after adjusting for all the covariates, revealed that "Avg-Dscore" and "Avg-DAS28" were the most significant factors contributing to final J-HAQ score, and confirmed the strong relationship between disease activity and functional disability. Conclusions: In patients with RA efficient disease management, by maintaining the DAS28 values at a level under 2.6, has significant association with improving functional capability. The threshold DAS28 level of 2.6 may be useful in developing targeted treatment guidelines for patients with RA.